A novel isoform of TET1 that lacks a CXXC domain is overexpressed in cancer. Issue 14 (22nd May 2017) - Good, Charly R.; Madzo, Jozef; Patel, Bela; Maegawa, Shinji; Engel, Nora; Jelinek, Jaroslav; Issa, Jean-Pierre J.
Abstract: TET1 oxidizes methylated cytosine into 5-hydroxymethylcytosine (5hmC), resulting in regulation of DNA methylation and gene expression. Full length TET1 (TET1 FL ) has a CXXC domain that binds to unmethylated CpG islands (CGIs). This CXXC domain allows TET1 to protect CGIs from aberrant methylation, but it also limits its ability to regulate genes outside of CGIs. Here, we report a novel isoform of TET1 (TET1 ALT ) that has a unique transcription start site from an alternate promoter in intron 2, yielding a protein with a unique translation start site. Importantly, TET1 ALT lacks the CXXC domain but retains the catalytic domain. TET1 ALT is repressed in embryonic stem cells (ESCs) but becomes activated in embryonic and adult tissues while TET1 FL is expressed in ESCs, but repressed in adult tissues. Overexpression of TET1 ALT shows production of 5hmC with distinct (and weaker) effects on DNA methylation or gene expression when compared to TET1 FL . TET1 ALT is aberrantly activated in multiple cancer types including breast, uterine and glioblastoma, and TET1 activation is associated with a worse overall survival in breast, uterine and ovarian cancers. Our data suggest that the predominantly activated isoform of TET1 in cancer cells does not protect from CGI methylation and likely mediates dynamic site-specific demethylation outside of CGIs.